1999
DOI: 10.1128/mcb.19.7.5096
|View full text |Cite|
|
Sign up to set email alerts
|

Atm Inactivation Results in Aberrant Telomere Clustering during Meiotic Prophase

Abstract: A-T (ataxia telangiectasia) individuals frequently display gonadal atrophy, and Atm؊/؊ mice show spermatogenic failure due to arrest at prophase of meiosis I. Chromosomal movements take place during meiotic prophase, with telomeres congregating on the nuclear envelope to transiently form a cluster during the leptotene/zygotene transition (bouquet arrangement). Since the ATM protein has been implicated in telomere metabolism of somatic cells, we have set out to investigate the effects of Atm inactivation on mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 99 publications
2
65
0
Order By: Relevance
“…Cells were fixed in 2% paraformaldehyde for 15 min, washed in 1ϫ PBS, permeabilized for 5 min on ice in 0.2% Triton X-100, and blocked in PBS with 1% bovine serum albumin. The procedure used for immunostaining is the same as that described previously (17)(18)(19).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed in 2% paraformaldehyde for 15 min, washed in 1ϫ PBS, permeabilized for 5 min on ice in 0.2% Triton X-100, and blocked in PBS with 1% bovine serum albumin. The procedure used for immunostaining is the same as that described previously (17)(18)(19).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, it has been shown that ATM function in¯uences on the fraction of telomeres anchored to the nuclear matrix (Smilenov et al, 1999). In somatic as well as germ cells de®cient in ATM function, more than 80% of the telomeric DNA is attached to the nuclear matrix, whereas in control cells about 50% is attached (Smilenov et al, 1999;Pandita et al, 1999). These results suggest that the major portion of telomeres in A-T cells is associated with the nuclear matrix.…”
Section: Atm De®ciency In¯uences Telomere Chromatin Structurementioning
confidence: 99%
“…This clustering of telomeres is thought to insure proper homolog pairing and synapsis of the homolog axes [60][61][62]. Interestingly both ATM [63] and more recently H2AX [29] have been shown to regulate the persistence of the telomere bouquet. The exit from the bouquet stage may therefore be coupled to the completion of the repair of meiotic DSBs.…”
Section: Role Of H2ax In Meiosismentioning
confidence: 99%